Techniques and Modes for Multi-Channel SAR Instruments - Younis, Marwan; De Almeida, Felipe Queiroz; López-Dekker, Paco; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2016)
SAR instruments with multiple transmit/receive channels allow for a variety of operation modes. The trade-space includes the instrument and antenna parameters designed to enable various techniques (operation modes). These are utilized to achieve a required SAR performance derived from the mission and user requirements. Finding a solution in this multi-dimensional trade space of inter-dependent parameters is not trivial and often involves the compromise of parameters. This paper addresses the topic of SAR instrument design tailored to a set of operation modes. It explains the SAR techniques and reports the performance highlighting possible compromises between techniques and system efficiency.
DLR Import::2019-04-03